Increased circulation time of Plasmodium falciparum underlies persistent asymptomatic infection in the dry season - Andrade, Carolina; Fleckenstein, Hannah; Thomson-Luque, Richard; Doumbo, Safiatou; Ferreira Lima, Náthalia; Anderson, Carrie L.; Hibbert, Julia; Hopp, Christine S.; Tran, Tuan M.; Li, Shanping; Niangaly, Moussa; Cisse, Hamidou; et al. (Nature medicine, 2020)
The dry season is a major challenge for Plasmodium falciparum parasites in many malaria endemic regions, where water availability limits mosquito vectors to only part of the year. How P. falciparum bridges two transmission seasons months apart, without being cleared by the human host or compromising host survival, is poorly understood. Here we show that low levels of P. falciparum parasites persist in the blood of asymptomatic Malian individuals during the 5- to 6-month dry season, rarely causing symptoms and minimally affecting the host immune response. Parasites isolated during the dry season are transcriptionally distinct from those of individuals with febrile malaria in the transmission season, coinciding with longer circulation within each replicative cycle of parasitized erythrocytes without adhering to the vascular endothelium. Low parasite levels during the dry season are not due to impaired replication but rather to increased splenic clearance of longer-circulating infected erythrocytes, which likely maintain parasitemias below clinical and immunological radar. We propose that P. falciparum virulence in areas of seasonal malaria transmission is regulated so that the parasite decreases its endothelial binding capacity, allowing increased splenic clearance and enabling several months of subclinical parasite persistence.
Das PDF enthält einen Anhang von 17 Seiten
Gesehen am 28.10.2020